THE MODERATION EFFECT OF INFORMATION SYSTEMS ON VOCATIONAL HIGH SCHOOL PRINCIPAL DECISION-MAKING MODEL - Didi Supriadi; Husaini Usman; Cepi Safruddin Abdul Jabar (LPMPP Universitas Negeri Yogyakarta, 2021)
A decision-making process in an organization is more effective if it is supported by reliable and valid information systems. Management Information System (MIS) and Decision Support System (DSS) are two systems commonly used by organizational leaders to collect information for making the Quality of Decision (QD). This study aimed to empirically investigate MIS influences on vocational high school principals’ QD. Besides, this study examined the moderation effect of the DSS on the decision-making processes. This quantitative research employed the survey method and purposive sampling technique. As many as 60 vocational high school principals and vice-principals in Yogyakarta, Indonesia were the participants of this study. They filled in questionnaires consisting of 19 items that were developed using the Likert scale. The quantitative data obtained were analyzed using Structural Equation Modeling. The research findings show that MIS has a significant effect on the quality of the decision-making process by vocational high school principals. However, for improving the decision quality, the model must be assisted by DSS as the moderator variable. MIS carries information required for principals while DSS provides data, model, and analysis instruments used for special cases in vocational high schools.